COVID-19 Mortality and Associated Factors in Patients with Chronic Kidney Disease on Dialysis: Cohort Analysis During the First Two Waves of the Pandemic - Rodriguez Mori, Juan E. (2025)
Introduction: The COVID-19 pandemic resulted in high global mortality rates, particularly among patients with comorbidities such as Chronic Kidney Disease (CKD) undergoing dialysis. Material and methods: This study included data from 310 CKD patients on dialysis in a Peruvian hospital during the first and second waves of the pandemic. It assessed in-hospital mortality and its associated factors, and evaluated the effectiveness of the International Severe Acute Respiratory and Emerging Infections Consortium (ISARIC4C) score as a predictive indicator of patient deterioration. Additionally, one-year post-discharge mortality and the main causes of death were analyzed. Results: In-hospital mortality among dialysis patients with COVID-19 was 48.71%. Admission to the ICU and male sex were associated with an increased risk of death. The ISARIC4C score appeared to be a valid predictor of clinical deterioration. No significant differences were found in mortality between the first and second waves. One-year post-discharge mortality was 22%, with cardiovascular disease, acute respiratory failure, and infectious diseases being the leading causes of death. Conclusions: The findings highlight the high vulnerability of dialysis patients with CKD during the COVID-19 pandemic. Although the ISARIC4C score is useful for predicting patient deterioration, it does not significantly impact long-term survival outcomes.